Solo keman için "Anadolu'nun yankıları" "echoes of Anatolia" for solo violin - Eker, Burak (Ankara: Müzik Eğitimi Yayınları, 2023)
Burak Eker'in solo keman için hazırladığı, temeline de öncü bestecimiz A. Adnan Saygun'un öznel mi öznel, eşsiz yapıtı Töresel Musıki'yi aldığı-dahası bu esere bir methiye, saygı duruşu mahiyetinde-son derece pratik, duru ve nitelikli bir çalışma. Anadolu'nun Yankıları aklımıza ilk gelebileceklerden çok daha fazlasına sahip: Sayısız entelektüel katmanıyla bu çalışmanın değeri, içine girildikçe artacak, dolaşıma sokuldukça pekişecektir, şüphesiz. Malzemesine içeriden bakabilen, temas etmekten, sese dökmekten geri durmayan; müzik biliminin, kompozisyonun ve icranın birbirinden kopuk olmadığı, bilâkis destekleyip birbirini tamamladığı böylesi bir üretimin varlık alanımız müziği önemseyen herkese ilham olması dileğiyle... / Echoes of Anatolia, a work by Burak Eker for solo violin based on the very special, unique work by the pioneering Turkish composer A. Adnan Saygun, Töresel Musıki (a translation of the title can't meet the hidden undertones such as traditional, customary, even rural and ritualistic, a. o.), is a quite practical, clear, limpid and qualified study which is also a respectful homage and tribute to Saygun. Echoes of Anatolia recalls far more than what its title easily evokes in mind: With its manifold intellectual layers, the worth and value of this work will undoubtedly increase as one delves into it and solidify once it circulates. May this production with its introspective attitude towards its musical material and fearless stand that could touch and transform it into sound; where musicology, composition and performance were dealt not as separate paths but supporting and completing each other, be an inspiration for everyone who values music, our realm of existence... / Prof. Dr. Hakkı Alper Maral
2
Keywords: Keman